(untitled) (The Pretoria Student Law Review, 2021)
The first part of this paper discusses the approach of the South African courts to socio-economic rights, arguing that it has resulted in limited progress in alleviating poverty. The Equality Court’s incorporation of equality law into socio-economic enquiries in Social Justice Coalition v Minister of Police could strengthen the case of claimants and override certain factors that cause the courts to defer to the executive, thus compelling the State to provide more immediate relief. This section also attempts to apply the prohibition of discrimination on the grounds of poverty to commercial entities. By understanding discrimination as the denial of advantages or opportunities, the argument that the economy and private companies depend on discriminating against the poor to function is advanced. The second part of the paper discusses the requirement that discrimination be unfair in order to be prohibited. It assesses the likelihood of courts finding that budgetary constraints and profit incentives are legitimate purposes served by discrimination on the grounds of poverty. Finally, the last part of this paper discusses whether antidiscrimination law is an appropriate tool for the eradication of poverty. Several criticisms of transformative constitutionalism, human rights discourse and anti-discrimination law are engaged with to show that anti-discrimination law, as it currently exists, will at most target incidents of poverty-based discrimination using moderate forms of relief that allow for the continuance of an oppressive capitalist order rather than creating systemic change. The courts will have to make radical decisions, which depart from conservative South African legal culture if the decision in Social Justice Coalition v Minister of Police is to have far reaching impact.